Design of patient rooms and automatic radioiodine-131 waste water management system for a thyroid cancer treatment ward: 'Suandok Model' - Vilasdechanon N. (Institute of Physics Publishing (IOP), 2015)
UNLABELLED: The great benefit of (131)I radionuclide treatment for differentiated thyroid cancer (DTC) was acknowledged by the long survival rate. The main requirements for (131)I therapy in hospital were treatment facilities and a radiation safety plan that assured radiation protection and safety to patient, hospital worker, public, and environment. OBJECTIVE: To introduce the concepts and methods of radiation safety design for a patient's room in a (131)I treatment ward and a system of radioactive waste water management in hospital. METHODS: The design was based on principles of external and internal radiation protection for unsealed source and radioactive waste management. Planning for treatment facilities was concluded from clinical evidence, physical and physiological information for (131)I, radiation safety criteria, hospital resources and budget. The three phases of the working process were: construction, software development, and radiation safety assessment. RESULTS: The (131)I treatment facility and automatic radioactive waste water management system was completely implemented in 2009. The radiation waste water management system known as the 'Suandok Model' was highly recommended by the national regulator to hospitals who desire to provide (131)I treatment for thyroid cancer. In 2011, the Nuclear Medicine Division, Chiang Mai University was rewarded by the national authority for a very good radiation practice in development of safe working conditions and environment. CONCLUSION: The Suandok Model was a facility design that fulfilled requirements for the safe use of high radiation (131)I doses for thyroid cancer treatment in hospital. The facility presented in this study may not be suitable for all hospitals but the design concepts could be applied according to an individual hospital context and resources. People who use or gain benefit from radiation applications have to emphasise the responsibility to control and monitor radiation effects on individuals, communities and the environment.